Theoretical Study on Surfactant Adsorption of Glycine Betaine on Gas-Liquid Interface - Zhang, Pingping; Zhang, Xue; Wang, Mingbo; Sun, Xiaomin (Asian Journal of Chemistry, 2014)
Glycine betaine is known as an excellent surfactant and osmolyte from organisms. To investigate the mechanism of glycine betaine, dodecyl hydroxypropyl sulfo betaine is chosen as an example to simulate its adsorption with water on gas-liquid interface by quantum chemistry. With the methods of B3LYP, highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are figured out and we find that LUMO of dodecyl hydroxypropyl sulfo betaine is more likely to gather to the positive charge center. Information of hydrogen bonds, charge change and bonding energy are listed, with the suggestion that number and postion of water impacts adsorption obviously.